2001
DOI: 10.1002/ccd.1172
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary interventions using a new 5 French guiding catheter: Results of a prospective study

Abstract: The aim of this prospective study was to analyze the technical feasibility, the success rate, and the special complications of percutaneous coronary interventions (PCIs) using a newly released 5 Fr guiding catheter with an inner diameter of 0.058". The study was performed in 150 consecutive patients subjected to coronary angioplasty. In 89% of the patients, the intervention was started with a 5 Fr catheter (JR4 or JL4); in 16 patients a 6 or 7 Fr catheter was used because of unstable clinical conditions accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
4
12
0
Order By: Relevance
“…The performance of 4‐Fr PCI, for example, required a certain learning curve [16]. In this study, however, the average procedure time, the average fluoroscopy time, and the contrast dye usage appeared comparable to those of previous reports using conventional 5‐Fr guiding catheters (36–45 min for procedure time, 10–16 min for fluoroscopy time, and 145–274 mL for contrast dye volume, respectively) [17–19]. Such comparable outcomes suggest that catheter manipulation of the virtual 3‐Fr system is not inferior to that of a regular 5‐Fr guiding catheter.…”
Section: Discussionsupporting
confidence: 68%
“…The performance of 4‐Fr PCI, for example, required a certain learning curve [16]. In this study, however, the average procedure time, the average fluoroscopy time, and the contrast dye usage appeared comparable to those of previous reports using conventional 5‐Fr guiding catheters (36–45 min for procedure time, 10–16 min for fluoroscopy time, and 145–274 mL for contrast dye volume, respectively) [17–19]. Such comparable outcomes suggest that catheter manipulation of the virtual 3‐Fr system is not inferior to that of a regular 5‐Fr guiding catheter.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, there was no comparative arm using a conventional sheath and GC system. Previous studies have confirmed that PCI using a conventional 5‐Fr sheath and GC system was technically feasible . Before the introduction of the Works system (5‐Fr sheathless GC) in our institution, PCI using conventional a 5‐Fr sheath and GC system was performed in 146 patients (160 lesions) from January 2008 to June 2010, and the clinical, angiographic, or procedural characteristics were similar to those in this study because the same operators performed PCI and chose the size of the GC (5‐Fr).…”
Section: Discussionsupporting
confidence: 69%
“…These restrictions have been reported to represent the predominant reason for radial spasms and postprocedural radial occlusions, especially if the radial diameter:sheath ratio is Ͻ 1.0 [2]. It is particularly among these patients that 5 Fr guiding catheter could help to improve procedural success rates and possibly reduce procedural failures and vascular access complications such as radial occlusions and hematomas, but 5 Fr, 0.058Љ lumen diameter guiding catheter affords less strength, visibility, and backup compared to 6 Fr [3]. Hence, we conducted a randomized study of 5 vs. 6 Fr transradial coronary interventions (TCI) in lesions not eligible to other than balloon angioplasty or stent implantation to ascertain whether 5 Fr has equivalent procedural success and complications rates as 6 Fr guiding catheter.…”
Section: Introductionmentioning
confidence: 93%